Comparison of classifications of hyperplastic endometrial lesions – World Health Organization and Endometrial Intraepithelial Neoplasia - Sobczuk, Anna; Wrona, Marcin (Menopause Review/Przegląd Menopauzalny, 2007)
Endometrial intraepithelial neoplasia (EIN) is a precursor to endometrioid endometrial adenocarcinoma characterized by monoclonal growth of mutated cells, a distinctive histopathologic appearance and 45-fold elevated cancer risk. The diagnosis of premalignant endometrial lesions remains non-standardized because the most widely used World Health Organization classification system is a poorly reproducible system, which does not specify objective architectural criteria for each category of hyperplasia and does not correspond to appropriate clinical management (under-treatment, over-treatment of lesions). The new proposed EIN diagnostic schema, based on an integrated morphological, genetic, molecular, objective histomorphometric scale (D-score) and clinical outcome studies, divides endometrial lesions into three categories: benign hyperplasia, endometrial intraepithelial neoplasia, and cancer.